The Darkness in Umairoh - Hasnul Insani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2009)
This research aims to find information about gender issues exploited by the author in The Jakarta Post short story ascribed by Yanusa Nugroho entitled Umairoh. The objectives of the research are 1. To investigate how women are described and positioned in the short story 2. To assess the implied attitudes of the author toward gender in the short story. 3. To identify the attitudes of the editors toward gender in the short story. The research results that; first women are described and positioned in the short story as suffered and powerless human beings. Second, the author implies that both women and men have ambivalent attitudes toward gender. Third, the editors let gender issues go to the public without qualification.